ANALYSIS OF WEBQUAL 4.0 AND COGNITIVE WALKTHROUGH METHODS ON CTI GOVIDEO SPARK HIRE ONLINE INTERVIEW APPLICATION - Apriyanthi, Ni Putu Eka; Gunadi, I Gede Aris; Sunarya, I Made Gede (Jurnal Teknik Informatika (Jutif), 2024)
This study aims to analyze the user experience quality of the CTI GoVideo Spark Hire online interview application, focusing on Safaga Indonesia institution. The research methodology employs Webqual 4.0 analysis and Cognitive Walkthrough as frameworks for evaluating application quality. Respondents were selected using Simple Random Sampling, and data were analyzed using reliability and internal consistency tests. The findings from the Webqual 4.0 analysis indicate that the majority of respondents rated the application positively, with 73% considering its quality to be good and 27% rating it as excellent. Internal consistency tests revealed overall high reliability, although the interaction variable showed relatively low values. Analysis using the Cognitive Walkthrough method revealed that 8 respondents were able to complete approximately 92.8% of the total 7 given task scenarios, with an average completion time of around 446 seconds or 7 minutes 26 seconds for all tasks. This evaluation holds significant relevance to Safaga Indonesia's need to enhance recruitment process efficiency.